2018
DOI: 10.3389/fsurg.2018.00066
|View full text |Cite
|
Sign up to set email alerts
|

Open Intraperitoneal Onlay Mesh (IPOM) Technique for Incisional Hernia Repair

Abstract: In an Expert Consensus Guided by Systematic Review the panel agreed that for open elective incisional hernia repair sublay mesh location is preferred, but open intraperitoneal onlay mesh (IPOM) may be useful in certain settings. Accordingly, the available literature on the open IPOM technique was searched and evaluated.Material and Methods: A systematic search of the available literature was performed in July 2018 using Medline, PubMed, and the Cochrane Library. Forty-five publications were identified as relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…For the open IPOM technique in incisional hernia repair a review revealed a recurrence rate of 12.6% (range 0–61%) at follow-up of 1–8.1 years (27). These outcome data based mainly on prospective and retrospective observational studies.…”
Section: Open Ipommentioning
confidence: 99%
“…For the open IPOM technique in incisional hernia repair a review revealed a recurrence rate of 12.6% (range 0–61%) at follow-up of 1–8.1 years (27). These outcome data based mainly on prospective and retrospective observational studies.…”
Section: Open Ipommentioning
confidence: 99%
“…This is why the laparoscopic IPOM procedure was abandoned. Even though the results of IPOM have been reported to be valuable for ventral hernias and rectus diastasis, there are still many publications showing adhesion formation due to intraperitoneal mesh placement and postoperative pain due to the application of tackers for mesh xation (18,19). The sublay technique requires opening the rectus sheath and involves a posterior layer of the rectus muscle in the in ammatory process of mesh ingrowth.…”
Section: Key Results and Interpretationmentioning
confidence: 99%
“…When evaluating overall complication rates, Sosin et al's [15] review highlights similar overall complication rates observed in ventral hernia repairs, which ranged from 32.6% to 39.1%, regardless of mesh location with no statistically significant difference (P = 0.738). While the onlay approach is generally considered the least technically challenging approach to mesh placement, it has fallen out of favor due to the reported increased wound and mesh infection complications [18] with approximately 7.6% of hernia repairs as of 2018 being performed in this plane. This is compared to greater than 65% of meshes being placed in the sublay-intraperitoneal, preperitoneal plane, or retromuscular plane in their pooled analysis of reported ventral hernia repairs [15] .…”
Section: Advantages and Current Datamentioning
confidence: 99%